Field of view extension and truncation correction for MR‐based human attenuation correction in simultaneous MR/PET imaging. Issue 2 (15th January 2014) - Blumhagen, Jan O.; Braun, Harald; Ladebeck, Ralf; Fenchel, Matthias; Faul, David; Scheffler, Klaus; Quick, Harald H.
Abstract : Purpose: : In quantitative PET imaging, it is critical to accurately measure and compensate for the attenuation of the photons absorbed in the tissue. While in PET/CT the linear attenuation coefficients can be easily determined from a low‐dose CT‐based transmission scan, in whole‐body MR/PET the computation of the linear attenuation coefficients is based on the MR data. However, a constraint of the MR‐based attenuation correction (AC) is the MR‐inherent field‐of‐view (FoV) limitation due to static magnetic field (B0 ) inhomogeneities and gradient nonlinearities. Therefore, the MR‐based human AC map may be truncated or geometrically distorted toward the edges of the FoV and, consequently, the PET reconstruction with MR‐based AC may be biased. This is especially of impact laterally where the patient arms rest beside the body and are not fully considered. Methods: : A method is proposed to extend the MR FoV by determining an optimal readout gradient field which locally compensates B0 inhomogeneities and gradient nonlinearities. This technique was used to reduce truncation in AC maps of 12 patients, and the impact on the PET quantification was analyzed and compared to truncated data without applying the FoV extension and additionally to an established approach of PET‐based FoV extension. Results: : The truncation artifacts in the MR‐based AC maps were successfully reduced in all patients, and the mean body volume was thereby increased by 5.4%. In some cases large patient‐dependent changes in SUV of up to 30% were observed in individual lesions when compared to the standard truncated attenuation map. Conclusions: : The proposed technique successfully extends the MR FoV in MR‐based attenuation correction and shows an improvement of PET quantification in whole‐body MR/PET hybrid imaging. In comparison to the PET‐based completion of the truncated body contour, the proposed method is also applicable to specialized PET tracers with little uptake in the arms and might reduce the computation time by obviating the need for iterative calculations of the PET emission data beyond those required for reconstructing images.